Service quality : SingTel and MobileOne. - Ho, Siew Poh. (2008)
In this research, the service quality of both companies will be determined and comparisons will be drawn to evaluate why M1 was able to gain a foothold in the telecommunications industry here despite the fact that it was much smaller and relatively inexperienced. Insights will be drawn using a modified version of the SERVQUAL model.